The Effect of the Application of Lean Production and Supply Chain Management on the Quality of Public Administration Services: (Case Study: Hussein Educational Hospital in Thi Qar) - Ahmed Karim Jassim (International Journal of Supply Chain Management, 2018)
Abstract- The effect of the use of lean production and supply chain management method to achieve quality of service in public administration unit in Thi Qar was studied in this research using the Hussein Educational Hospital as a case study. The workers in the Hall of operations at the hospital are selected for interview while questionnaires were distributed to the selected workers. After analysis of the results collected, the study found that there is a presence of correlation and significance statistically between the variables of the study: lean production, supply chain management, quality of service. It found that there is an effect of changes in lean production system and supply chain management on the quality of the service. The study of the result analysis also showed that the affected system changes the result of the application of the service quality as an increase in one unit of the independent variables (output slim) affects the increase in the value of the quality of service at the hospital by (1.19) and the value of Beta by (0.766). This signifies the significant relationship between the lean production system and supply chain management and the quality of services in the general hospital. Finally, conclusion and recommendations of the study were presented. Keywords- lean production system, supply chain management, applications, quality of service, Hussein Educational Hospital.